Design and Develop Model for Cable Pulling Machine using 0.37kW Motor - Katimon, Mohd Nizam; Johari, Muhammad Nur Iman (Research Progress in Mechanical and Manufacturing Engineering, 2023)
A cable pulling machine is a machine that helps in the installation of cable into an oil and gas platform's electrical system. There are numerous types of cable pulling machines available on the market, but none of them are appropriate for installing cable on an oil and gas platform. Because there was no suitable machine available, the cable installation was done by hand. There is no problem with small size cable, but when larger size cable is involved, too much manpower is wasted to install the cable. This project is being completed to assist the company in improving the cable installation process. To complete this project, three phases were created: conceptual design, embodiment design, and detailed design. On the other hand, engineering analysis must be developed alongside component simulation, and this requires formula calculation and Solidworks features. The results of component analysis and simulation are crucial for assessing the performance and quality of the final product. The studies showed that this machine can pull cables at the necessary 34.5 rpm speed and 10.4 kgm torque for cable installation. This design is expected to be a practical help for workers installing cable for the electrical system of the oil and gas platform.